Social Media as the Fifth Estate of Conflict Resolution in Indonesia: A Netnography Study on Digital Activism #PeringatanDarurat - Aristyavani, Inadia; Julianto, Edi Nurwahyu; Taryana, Ade; Anwar, Miftahol; Jamalullail, Jamalullail (Mahesa Research Center, 2025)
The Research discusses how digital media can be used as a fifth estate. The fifth pillar refers to the function of social media as a supervisor of public policies or issues. This supervision is through netizens' activities to encourage policymakers to act appropriately. Digital media platforms provide a new space for individuals and groups to share information, self-organize, and influence public policy. This form of supervision is through expressions of disappointment and anger over several social and political situations. The Research uses digital media theory as the fifth pillar of William Dutton. The case studied is the #PeringatanDarurat movement. This case is critical because it relates to a violation of the Constitution. The case began with the government's and the DPR's plan to make an Election Bill contrary to the Constitutional Court's (MK) decision. The Research uses the ethnography method. The data analyzed was Twitter (X) social media user posts. Data collection is carried out through 2 forms: immersion and investigation. Immersion was carried out by observing social and medical user X. The investigation collected posts about #PeringatanDarurat. The data was processed using thematic analysis. The study results show four main themes of social media user posts. First, the manipulation of rules and the Constitution. Second, anger against oligarchs. Social media users expressed outrage at the power that no longer represented the people. Third, social media users call for teenagers to be politically literate. Fourth, a collective invitation to take action together. This Research shows the role of social media as the fifth pillar (the fifth estate). Social media has become the primary means of spreading political awareness and social mobilization.